Frequency of Gallstones in Anti-HCV Antibody Positive Patients in a Tertiary Care Hospital of Larkana - Azizullah Jalbani, Azizullah Jalbani; Hakim Ali Abro, Hakim Ali Abro; Chandur Lal, Chandur Lal; Sultan Ahmed , Sultan Ahmed; Abdul Wahab Sheikh, Abdul Wahab Sheikh; Vishamber Lal, Vishamber Lal (Students' Supplement of Journal of Rawalpindi Medical College, 2019)
Background: Gallstones being one of the common digestive disorders, are a major burden on public health resources. There is a high prevalence of gallstones in HCV positive patients in USA. There is a second highest prevalence of HCV infection in Pakistan after Egypt. Objectives: To determine the frequency of gallstones in Anti-HCV Antibody positive patients at a tertiary care hospital of Larkana. Methods: This is an Observational Cross-sectional study. Study was carried out from December 2017 to December 2018 at Department of Medicine, Chandka Medical College Teaching Hospital, Larkana. Patients who visited medical OPD for treatment of Hepatitis C had abdominal ultrasonological examination performed by a senior consultant radiologist, who especially looked for gallstones. Diagnosis of gallstones was confirmed by radiologist. Results: Total 160 patients were included in study, 97 (60.6%) of whom were male and 63 (39.4%) were female. Gallstones were present in 28 (17.5%) cases. Gallstones positive males were 11 (11.3%) and females were 17 (27%). Gallstones were found to be more common in women. Conclusion: HCV infection may be a risk factor for developing gallstones in younger patients. Keywords: Gallstones, HCV, Extrahepatic Manifestations.